ASEAN at 45 : a case for principled realism - Ho, Benjamin Tze Ern (2012)
Regional flare-ups over territorial sovereignty have placed ASEAN’s cohesion and solidarity under the spotlight. The ability of ASEAN to stay neutral in its own backyard is increasingly challenged by the clashing interests of big powers. ASEAN states should temper the pursuit of national interests with established principles.